Daya Hambat Protaderma terhadap Fusarium sp. Penyebab Penyakit Layu pada Tomat - Andi Resti Resti; Yusriadi Marsuni Marsuni (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Fusarium wilt disease in tomato plants (Solanum lycopersicum) is one of the main obstacles causing a decrease in tomato production. Control of this disease generally still relies on the use of chemical fungicides which in the long term can have a negative impact on the environment. Environmentally friendly control efforts need to be developed by biological agents. One product that has the potential to be used is Protaderma, a biofungicide based on Trichoderma sp. which functions to suppress the growth of pathogens and increase plant resistance. This research aims to determine the effectiveness of Protaderma in inhibiting the growth of Fusarium sp., determine the most effective dose, and see its effect on the growth of tomato plant height. Testing was carried out in vitro using the dual culture method and field testing using a Completely Randomized Design (CRD) with 6 treatments and 3 replications. This treatment included control (without Protaderma) and application of Protaderma with five different doses, namely 5 g, 10 g, 15 g, 20 g and 25 g per plant. The results show that Protaderma is able to inhibit the growth of Fusarium sp. amounted to 60.8%, reduced the incidence of disease from 55.6% to 0% at doses of 20 g and 25 g, and increased plant height to an average of 59.78 cm at a dose of 25 g.